Edamame caspian sea soygurt as plant-based yogurt alternatives - Kusnadi, Joni; Septi, Nur Diana; Fibrianto, Kiki (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Caspian sea soygurt is made by fermenting edamame milk with Lactococcus lactis ssp. cremoris and Acetobacter orientalis as microbial cultures. To produce good soygurt, edamame milk fermentation requires ideal conditions, such as an optimum carbon source and starter concentration. This study aimed to determine the effect of the proportion of sucrose:skim and concentration of starter on the physical, chemical, microbiological, and sensory characteristics of Caspian sea soygurt. This study used a randomized block design with 2 factors: sucrose:skim proportion (2.5:7.5, 5:5 7.5:2.5) and starter concentration (8, 10, 12% of pasteurized edamame milk) repeated three times. Data were analyzed using ANOVA and continued with the Tukey test. These results was used to select the best treatment using the Zeleny Multiple Attribute Method. The best Caspian soygurt treatment was found in the proportion of sucrose:skim 5:5 (% w/v of pasteurized edamame milk) and starter concentration 12 (% v/v of pasteurized edamame milk), which produced a color (L*) 78.98, (a*) -2.86 ( b*) 23.79, viscosity 516.67 cP, protein 3.38%, antioxidant activity 43.12%, pH 4.35, total lactic acid bacteria 9.85 log CFU/mL with a preference level of 3.45 and an acceptance level of 3.55 for the greenness, a preference level of 3.79 and an acceptance level of 3.80 for the brightness, a preference level of 3.15 and an acceptance level 3.21 on the sour aroma, preference level of 3.04 and acceptance level of 3.11for the beany aroma, preference level of 3.04 and acceptance level of 3.18 for the beany flavor, preference level of 3.02 and acceptance level of 3.19 for the sour taste, preference level of 2.98 and acceptance level of 3.09 for sweet taste, preference level of 3.49 and acceptance level of 3.60 for the viscosity.